2016
DOI: 10.1159/000450859
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Uveal Melanoma following Intravitreal Bevacizumab

Abstract: Purpose: Typically treatment of large melanomas (by Collaborative Ocular Melanoma Study criteria) is restricted to enucleation, due to size constraints for plaque brachytherapy. Because primary and metastatic uveal melanoma cells are inhibited by bevacizumab (an anti-vascular endothelial growth factor), this prospective study evaluated the impact of intravitreal bevacizumab on large uveal melanomas that were destined for enucleation. Size reduction by bevacizumab would potentially salvage these eyes by making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…As a matter of fact, such treatment is reported to even promote expansion of melanoma cells in vitro (Dithmer et al, 2017 ). Furthermore, neoadjuvant intravitreous injection of this VEGF trap failed to shrink large size melanoma and is even counter indicated in these cases because it may instead even promote melanoma growth (Francis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, such treatment is reported to even promote expansion of melanoma cells in vitro (Dithmer et al, 2017 ). Furthermore, neoadjuvant intravitreous injection of this VEGF trap failed to shrink large size melanoma and is even counter indicated in these cases because it may instead even promote melanoma growth (Francis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We were concerned, as such tumor growth could be a possible adverse effect of bevacizumab. Recently, similar cases of paradoxical enlargement were reported in patients with uveal melanoma after IVB [32]. They used IVB as a neoadjuvant concept for treating uveal melanoma, but observed that the tumor size increased rather than decreased, and the study was terminated early.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, in vivo and in vitro studies showed that twistrelated protein 1 (Twist1), neurogenic locus notch homolog protein 4 (Notch4), hypoxia inducible factor (HIF)-1a , EPH receptor A2 (EphA2), matrix metalloproteinase (MMP)-1, 2, -9, -14, and vascular endothelial (VE)-cadherin are potential therapeutic targets and prognostic indicators in VM+ tumor samples [22,56]. Moreover, these studies suggest that VM+ tumor samples were resistant to common antiangiogenic drugs, such as apatinib, bevacizumab, and sunitinib [23,34,57]. The high ratio of neovascularization in VM+ tumor promotes angiogenesis, metastasis, and tumor growth along with extensive hypoxia and necrosis as well as induced recruitment of various pro-angiogenic factors, such as bone marrow-derived CD45 + myeloid cells, pericyte progenitor cells, and mature F4/80 + tumor-associated macrophages [58,59].…”
Section: Discussion 10mentioning
confidence: 99%